Kulturowe konsekwencje naukowego badania religii - Sztajer, Sławomir (Polskie Towarzystwo Religioznawcze, 2010)
Sławomir Sztajer – CULTURAL CONSEQUENCES OF THE SCIENTIFIC STUDY OF RELIGION Although the study of religion constitutes a well established field of inquiry, there are still researchers who call for a truly scientific approach to religion. Since the second half of the 19th century, when the science of religion came into being, the scientific status of some approaches to the study of religion has been repeatedly called into question. Today, there are many scientists of reli-gion who claim that the scientific study of religion is not only possible but it is also necessary if one wants to explain religious phenomena. The scientific study of religion has important cultural consequences which can be seen as side effects of scientific research. Among them, one can point out changes of religiosity; disturbance of the balance between the institutionalized scientific-technological approach to the world and a tendency to search a deeper meaning of existence which realizes itself in religion; orientation towards instrumental values instead of ultimate ones; the main-tenance of the dominant focus on what is here and now instead of on transcendence. There are, however, limitations of the influence which scientific study of religion exercises over culture.